Crystal structure of a novel homodimeric l‐ribulose 3‐epimerase from Methylomonus sp. Issue 6 (1st May 2021) - Yoshida, Hiromi; Yoshihara, Akihide; Kato, Shiro; Mochizuki, Susumu; Akimitsu, Kazuya; Izumori, Ken; Kamitori, Shigehiro
Abstract : d ‐Allulose has potential as a low‐calorie sweetener which can suppress fat accumulation. Several enzymes capable of d ‐allulose production have been isolated, including d ‐tagatose 3‐epimerases. Here, we report the isolation of a novel protein from Methylomonas sp. expected to be a putative enzyme based on sequence similarity to ketose 3‐epimerase. The synthesized gene encoding the deduced ketose 3‐epimerase was expressed as a recombinant enzyme in Escherichia coli, and it exhibited the highest enzymatic activity toward l ‐ribulose, followed by d ‐ribulose and d ‐allulose. The X‐ray structure analysis of l ‐ribulose 3‐epimerase from Methylomonas sp. (MetLRE) revealed a homodimeric enzyme, the first reported structure of dimeric l ‐ribulose 3‐epimerase. The monomeric structure of MetLRE is similar to that of homotetrameric l ‐ribulose 3‐epimerases, but the short C‐terminal α‐helix of MetLRE is unique and different from those of known l ‐ribulose 3 epimerases. The length of the C‐terminal α‐helix was thought to be involved in tetramerization and increasing stability; however, the addition of residues to MetLRE at the C terminus did not lead to tetramer formation. MetLRE is the first dimeric l ‐ribulose 3‐epimerase identified to exhibit high relative activity toward d ‐allulose. Abstract : d ‐Allulose has potential as a low‐calorie sweetener which can suppress fat accumulation. The enzymes capable of d ‐allulose production have attracted attention. Here, we report the X‐ray structure of a novel l ‐ribulose 3‐epimerase from Methylomonas sp. (MetLRE) which also has enzymatic activity towards d ‐allulose, showing that MetLRE is the first dimeric l ‐ribulose 3‐epimerase identified to exhibit high relative activity toward d ‐allulose.